2000
DOI: 10.1177/0092070300281014
|View full text |Cite
|
Sign up to set email alerts
|

Agency and Trust Mechanisms in Consumer Satisfaction and Loyalty Judgments

Abstract: The authors propose a framework for understanding key mechanisms that shape satisfaction in individual encounters, and loyalty across ongoing exchanges. In particular, the framework draws together two distinct approaches: (1) agency theory, rooted in the economic approach, that views relational exchanges as encounters between principals (consumers) and agents (service providers) and (2) trust research that adopts a psychological approach toward consumer-provider relationships. In so doing, the authors specify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

48
859
1
50

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,265 publications
(958 citation statements)
references
References 59 publications
48
859
1
50
Order By: Relevance
“…Therefore, Singh and Sirdeshmukh [25] divided the trust construct into two parts which consisted pre-purchase performance expectations and post-purchase performance evaluations among agency and trust mechanisms, and it validated that the satisfaction had significant positive effect on post-purchase performance evaluations.…”
Section: Research Hypothesesmentioning
confidence: 96%
See 2 more Smart Citations
“…Therefore, Singh and Sirdeshmukh [25] divided the trust construct into two parts which consisted pre-purchase performance expectations and post-purchase performance evaluations among agency and trust mechanisms, and it validated that the satisfaction had significant positive effect on post-purchase performance evaluations.…”
Section: Research Hypothesesmentioning
confidence: 96%
“…Many previous studies demonstrated the importance of satisfaction in behaviour assessment, showing that it has positive effect on the behaviour intention and trust [23][24][25]. Satisfaction has been noted as a special form of consumer attitude.…”
Section: Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The technical component of quality shows the outcome obtained by the customer by using the service whereas the functional component reflects the relation between the customer and the organization and the assessment of the place (or environment) where the service was provided (Grönroos, 1990). Tangible and intangible constituents of quality were important in evaluating either customer view of an organization or trust (Doney & Cannon, 1997;Garbarino & Johnson, 1999;Singh & Sirdeshmukh, 2000).…”
Section: Loyalty and Value Equitymentioning
confidence: 99%
“…There are controversial data about the link of primary level antecedents with loyalty or secondary level antecedents. Some authors proved that price as a primary level antecedent influences customer satisfaction and has an effect on loyalty through satisfaction (Bolton & Lemon, 1999); other authors argue that price has an effect on trust and loyalty (Singh & Sirdeshmukh, 2000). There is no consensus as to the components of the primary level antecedents of customer loyalty (e.g.…”
Section: Loyalty and Value Equitymentioning
confidence: 99%